EVALUASI PROGRAM KELUARGA HARAPAN (PKH) DI KELURAHAN PERIUK JAYA KECAMATAN PERIUK KOTA TANGERANG - Nufus, Hayati; Khikmawanto (iLearning Journal Center, 2023)
ABSTRACT This research aims to evaluate the implementation of the Program Keluarga Harapan (PKH) in Periuk Jaya Sub district, Periuk District, Tangerang City, using descriptive qualitative research method involving observation, interviews, and data interpretation. Research informants include various stakeholders in the PKH implementation, including high-ranking officials such as the Head of the Tangerang City Social Office, the Coordinator of PKH in Tangerang City, and PKH beneficiaries. The research results indicate that the implementation of PKH in Periuk Jaya has achieved various levels of success, especially in improving the health and education quality of the beneficiaries, supported by their active participation. Despite changes in fund disbursement, efficiency can still be improved through better guidance. Issues regarding the adequacy of assistance and equitable distribution persist, emphasizing the importance of refining beneficiary selection. The positive response from the community towards PKH demonstrates its positive impact, although there is room for improvement. Overall, this research provides a comprehensive overview of the implementation of PKH in Periuk Jaya..